PENGARUH PERKEMBANGAN PRODUK KAIN TENUN SONGKET LOKAL DAN KREATIVITAS PENGRAJIN TERHADAP MINAT MASYARAKAT KOTA PALEMBANG - Nina Fitriana; Firdaus Sianipar; Dian Triana Resti (JURNAL KOMPETITIF, 2017)
This study aims to know, analyze and prove the effect of the development of local songket woven fabrics and creativity of craftsmen to the interests of the people of Palembang.Sampel this study as many as 74 respondents. The analysis technique used is multiple linear regression analysis. The result of the research shows that there is influence of the development of the local songket woven cloth product to the interest of the people of Palembang city and there is no influence to the creativity of the craftsmen to the interest of the people of Palembang city (case study of craftsmen at Ki Gede Ing Suro Street). Multiple linear regression equation is Y = 25,607 + 0,342X1 -0,54x2. Based on the results of the test results of regression coefficient simultaneously obtained f count of 8.944 is greater than f table of 3.12. At test X1 regression coefficient partially obtained t count equal to 4,224 bigger than t table 0,235, hence development of local songket woven fabric product partially there is significant positive influence to interest of society of Palembang city. At test X2 regression coefficient partially obtained t count equal to -.309 smaller than t table 0,235. then the creativity of craftsmen partially no significant positive effect on the interest of the community of Palembang.Hasil value coefficient of determination (R²) of 0.201 or as much as 20.1% variable interest community (Y) influenced the development of local songket woven (X1). The rest of 79.9% is influenced by other variables that are not researched.Keywords: Product development, Creativity, Interests